Overexpression of Annexin A1 Is an Independent Predictor of Longer Overall Survival in Epithelial Ovarian Cancer - MANAI, MAROUA; DOGHRI, RAOUDHA; FINETTI, PASCAL; MRAD, KARIMA; BOUABSA, RIHAB; MANAI, MOHAMED; BIRNBAUM, DANIEL; BERTUCCI, FRANÇOIS; CHARFI, LAMIA; DRISS, MAHA (In vivo (Athens), 2020)
Epithelial ovarian cancer (EOC) is the major gynecological cause of cancer deaths. Annexin A1 (ANXA1) protein has been implicated in the aggressiveness of several cancer types. This study retrospectively assessed ANXA1 expression in epithelial cells of 156 pre-chemotherapy EOC samples and 34 normal ovarian samples from patients treated at Salah Azaiez Institute. Using immunohistochemistry, ANXA1 expression was compared in normal versus cancer samples; correlations with clinicopathological features, including overall survival, were sought. Fifty-two percent of tumor samples showed epithelial ANXA1 staining versus only 26% of normal samples (Fisher's exact test, p=0.00794). Epithelial ANXA1 expression was correlated with better overall survival in both univariate and multivariate analyses. The possible contribution of ANXA1 overexpression to EOC outcome may be relevant to therapeutic strategies.